Low-intensity pulsed ultrasound in obstetrics and gynecology: advances in clinical application and research progress - Ji, Xiaoyu; Duan, Hua; Wang, Sha; Chang, Yanan (Frontiers in Endocrinology, 2023)
In the past decade, research on ultrasound therapy in obstetrics and gynecology has rapidly developed. Currently, high-intensity ultrasound has been widely used in clinical practice, while low-intensity ultrasound has gradually emerged as a new trend of transitioning from pre-clinical research to clinical applications. Low-intensity pulsed ultrasound (LIPUS), characterized by a non-invasive low-intensity pulse wave stimulation method, employs its non-thermal effects to achieve safe, economical, and convenient therapeutic outcomes. LIPUS converts into biochemical signals within cells through pathways such as cavitation, acoustic flow, and mechanical stimulation, regulating molecular biological mechanisms and exerting various biological effects. The molecular biology mechanisms underlying the application of LIPUS in obstetrics and gynecology mainly include signaling pathways, key gene expression, angiogenesis, inflammation inhibition, and stem cell differentiation. LIPUS plays a positive role in promoting soft tissue regeneration, bone regeneration, nerve regulation, and changes in cell membrane permeability. LIPUS can improve the treatment benefit of premature ovarian failure, pelvic floor dysfunction, nerve damage caused by intrauterine growth restriction, ovariectomized osteoporosis, and incomplete uterine involution through the above biological effects, and it also has application value in the adjuvant treatment of malignant tumors such as ovarian cancer and cervical cancer. This study outlines the biological mechanisms and applications of LIPUS in treating various obstetric and gynecologic diseases, aiming to promote its precise application and provide a theoretical basis for its use in the field.